How to set up your google scholar profile: A brief technical guide - Himel Mondal; Sarika Mondal; Shaikat Mondal (Wolters Kluwer Medknow Publications, 2022)
Google Scholar is a free search engine that provides information about scholarly articles available on the Internet. An author can track the citations and other author-level metrics such as the h-index and i10-index in the Google Scholar profile. Opening an account in Google Scholar is free. An author can open the account with the Google account (e. g., Gmail account credential) details. If an institutional e-mail address is available, the author can verify the e-mail address. However, this is not a prerequisite for opening an account. In this article, we provide a brief technical guide on the creation of a Google Scholar profile.